Simultaneous multi-nuclide imaging via double-photon coincidence method with parallel hole collimators - Mizuki Uenomachi; Kenji Shimazoe; Kenichiro Ogane; Hiroyuki Takahashi (Scientific Reports, 2021)
Abstract Multi-tracer imaging can provide useful information in the definitive diagnosis and research of medical, biological, and pharmaceutical sciences. Single-photon emission computed tomography (SPECT) is one of the nuclear medicine imaging modalities widely used for diagnosis or medical research and has a multi-tracer imaging capability. One of the drawbacks of multi-tracer imaging is crosstalk from other gamma rays, which affects the reconstructed image. Scattering correction methods, such as the dual- and triple-energy window methods, are used for conventional SPECT imaging to reduce the background caused by the crosstalk. This study proposes another crosstalk reduction method. Some nuclides emit two or more gamma rays through intermediate levels. Thus, detecting these gamma rays with the coincidence method allows us to distinguish a true gamma ray signal and a background signal. The nuclide position can be estimated at the intersection of two gamma rays using collimators. We demonstrate herein simultaneous 111In and 177Lu imaging via the double-photon coincidence method using GAGG detectors and parallel hole collimators. The double-photon coincidence method greatly reduces the background caused by other gamma rays and offers higher-quality images than does conventional imaging.